2015
DOI: 10.3892/ol.2015.3366
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression as an independent indicator of poor prognosis for patients with anaplastic thyroid cancer

Abstract: Abstract. The protein nestin, a neuronal stem cell marker, has been reported to indicate a poor prognosis in various tumours. Anaplastic thyroid cancer (ATC) is one of the most aggressive malignancies in humans, and its molecular background has not been identified. The present study evaluated the expression of nestin and its significance in ATC. Tissue samples from 23 patients with ATC were subjected to immunohistochemical staining and the staining intensity of nestin in the cytoplasm was evaluated. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Analysis of NESTIN protein expression in 23 ATC patients showed that only 26.1% of samples were NESTIN-positive. Meanwhile, patients with positive expression of NESTIN had a worse outcome compared to NESTIN-negative individuals, suggesting a potential prognostic value for this marker in patients with ATC [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of NESTIN protein expression in 23 ATC patients showed that only 26.1% of samples were NESTIN-positive. Meanwhile, patients with positive expression of NESTIN had a worse outcome compared to NESTIN-negative individuals, suggesting a potential prognostic value for this marker in patients with ATC [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the undifferentiated human carcinomas, ATC is causes frequent mortality; patients diagnosed with ATC exhibit a mean survival of ~6 months (1). ATC is aggressive and characterized by highly invasive behavior and early distant metastasis (19). The 5-year survival rate of ATC has been reported to be <5% (2).…”
Section: Discussionmentioning
confidence: 99%
“…Observations in several malignancies suggest that nestin may serve as a central organizer of important processes for cancer behavior. Nestin expression in tumor tissue has been associated with the degree of tumor differentiation and proliferation, the invasive and metastatic capacities of tumors and/or the degree of neoangiogenesis [ 60 , 61 , 62 ].…”
Section: Nestin-expressing Cells In Lung Cancermentioning
confidence: 99%